Practical Scala DSLs Real-World Applications Using Domain Specific Languages - Riti, Pierluigi (Apress, 2018)
Build domain specific languages (DSLs) using Java's most popular functional programming language: Scala. This book introduces the basics of Scala and DSLs using a series of practical examples. In each chapter of Practical Scala DSLs, you'll learn to create pragmatic and complete code examples that explain the actual use of DSLs with Scala: a web API and microservices; a custom language; a mobile app; a Forex system; a game; and cloud applications. At the end of this unique book, you'll be able to describe the differences between external and internal DSLs; understand when and how to apply DSLs; create DSLs using Scala; and even create a DSL using another programming language. You will: Build DSLs in Scala Write a web API and microservices Create a custom language Apply DSLs to mobile apps development, a Forex trading system, game development, and more Discover the role of DSLs in cloud development Integrate DSLs as part of a DevOps program or structure Build internal and external DSLs.